Working Memory and Language Contribution to Verbal Learning and Memory in Drug-Resistant Unilateral Focal Temporal Lobe Epilepsy - Bolocan, Monica; Iacob, Claudia I.; Avram, Eugen (Frontiers in Neurology, 2021)
We aimed to investigate the working memory and language separate contributions to verbal learning and memory in patients with unilateral drug-resistant temporal lobe epilepsy (drTLE); additionally, we explored the mediating role of working memory on the relationship between the number of antiepileptic drugs (AED) and short-term verbal memory. We retrospectively enrolled 70 patients with left (LTLE; n = 44), and right (RTLE; n = 26) drTLE. Forty similar healthy controls were used to determine groups’ impairments at working memory, language, and various stages of verbal learning and memory measures (e.g. the first and the last list-learning trial, and delayed-recall; story memory). Regression analyses were used to assess the contribution of potential predictors while controlling for main clinical and demographic variables, and to ascertain the mediating role of working memory. Patients had impaired working memory and story memory, while only LTLE showed language and verbal learning deficits. In RTLE, language was the unique predictor for most verbal learning measures, while working memory predicted the story memory performance. In LTLE, working memory contributed to the list-learning short-term measures and mediated the interaction between AED number and these measures, while language predicted the delayed-recall. Finally, working memory confounds performance at short-term memory measures in both groups. Working memory is impaired in drTLE and contributes to the verbal memory and learning deficits, in addition to language, mediating the relationship between AED number and short-term verbal memory in left drTLE. Clinicians should consider this overlap when interpreting poor performance at verbal learning and memory.